IMPLEMENTASI KEPEMIMPINAN TRANSFORMASIONAL PADA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN JAYAPURA - Hidayat, Wagus; Aedah, Nur; Saa, Septinus (Universitas Cenderawasih, 2023)
This research aims to implement transformational leadership in the Secretariat of the Regional People's Representative Council of Jayapura Regency. Then it describes what factors support and hinder the implementation of transformational leadership in realizing good governance at the Secretariat of the Regional People's Representative Council of Jayapura Regency. As well as formulating the efforts made to realize good governance at the Secretariat of the Regional People's Representative Council of Jayapura Regency. This research uses qualitative descriptive research. The determination of key informants was done purposefully by selecting Sekwan as the key informant. The data collection techniques used were in-depth interviews and observation. Data analysis includes the stages of data reduction, data presentation, and drawing conclusions. The research findings show that transformational leadership in realizing good governance in Sekwan's environment is implemented in three steps. First, through the example and firmness of the leadership. Second, the orientation of Sekwan leadership leads to the formation of democratization by intensifying discussions and enforcing rules that bind all human resources in the Jayapura Regency DPRD Secretary. The supporting factors are the authority of the leaders, the level of education of qualified human resources, and the existence of collaborative cooperation. Meanwhile, the inhibiting factors are that the leadership is not yet fully democratic, the apathetic attitude of the leaders, and the inefficient use and planning of time. Efforts to reform bureaucracy, implement and adhere to rules and discipline, require efforts to prioritize dynamic patterns of attitudes toward resource needs.